Walt Whitman : words for America - Kerley, Barbara; Selznick, Brian (New York : Scholastic Press, 2004)
A biography of the American poet whose compassion led him to nurse soldiers during the Civil War, to give voice to the nation$1 (Bs grief at Lincoln$1 (Bs assassination, and to capture the true American spirit in verse.s
Keywords: Whitman, Walt, -- 1819-1892 -- Juvenile literature; Whitman, Walt, -- 1819-1892.; Poets, American -- 19th century -- Biography -- Juvenile literature; Nurses -- United States -- Biography -- Juvenile literature; Poets, American; Nurses; United States -- History -- Civil War, 1861-1865 -- Medical care -- Juvenile literature; United States -- History -- Civil War, 1861-1865.